Automated sorting of polymer flakes: Fluorescence labeling and development of a measurement system prototype. (April 2015) - Brunner, S.; Fomin, P.; Kargel, Ch.
Highlights: Identification of waste polymers based on incorporated fluorescence tracers. Approx. 1800 small plastic flakes/s (corresponds to approx. 300 kg/h) can be handled. Classification performance and throughput were quantified using three polymer types. The measurement system showed an average sensitivity of 99.4% and precision of 99.5%. Abstract: The extensive demand and use of plastics in modern life is associated with a significant economical impact and a serious ecological footprint. The production of plastics involves a high energy consumption and CO2 emission as well as the large need for (limited) fossil resources. Due to the high durability of plastics, large amounts of plastic garbage is mounting in overflowing landfills (plus 9.6 million tons in Europe in the year 2012) and plastic debris is floating in the world oceans or waste-to-energy combustion releases even more CO2 plus toxic substances (dioxins, heavy metals) to the atmosphere. The recycling of plastic products after their life cycle can obviously contribute a great deal to the reduction of the environmental and economical impacts. In order to produce high-quality recycling products, mono-fractional compositions of waste polymers are required. However, existing measurement technologies such as near infrared spectroscopy show limitations in the sorting of complex mixtures and different grades of polymers, especially when black plastics are involved. More recently invented technologies based on mid-infrared, Raman spectroscopy or laser-aided spectroscopy are still under development and expected to be rather expensive. A promising approach to put high sorting purities into practice is to label plastic resins with unique combinations of fluorescence markers (tracers). These are incorporated into virgin resins during the manufacturing process at the ppm (or sub ppm) concentration level, just large enough that the fluorescence emissions can be detected with sensitive instrumentation but neither affect the visual appearance nor the mechanical properties of the polymers. In this paper we present the prototype of a measurement and classification system that identifies polymer flakes (mill material of a few millimeters size) located on a conveyor belt in real time based on the emitted fluorescence of incorporated markers. Classification performance and throughput were experimentally quantified using 3 different types of polymers (Polyoxymethylene (POM), Polybutylenterephthalat (PBT) and Acrylonitrile Styrene Acrylate (ASA)) in colored and uncolored form. Overall, 12 classes of plastic flakes were investigated in this study, where 11 classes were labeled with unique binary combinations of 4 fluorescence markers and class 12 includes unlabeled plastic flakes of various colors. From approx. 68, 000 investigated flakes it was found that the developed measurement prototype system achieves an average sensitivity (true positive rate) of 99.4% and a precision (positive predictive value) of 99.5%, while being able to handle up to approx. 1800 flakes per second.